2001
DOI: 10.1016/s0048-9697(01)00740-9
|View full text |Cite
|
Sign up to set email alerts
|

Pet dogs as sentinels for environmental contamination

Abstract: The presence of environmental contaminants in air, water and food may pose significant health risks to the exposed human population. However, problems associated with assessing chronic exposure to low doses of environmental chemicals, multiple exposure routes, diseases with long latency periods, and non-specific health outcomes make it difficult to conduct the appropriate human epidemiologic studies. It may be useful to complement human epidemiology with animal studies. Animals monitored or evaluated in situ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 10 publications
3
55
0
6
Order By: Relevance
“…This might be a result of higher levels of p,p'-DDE and both α-and β-HCH in their blood. Sub-optimal lymphoproliferative activity (i.e., decreased responses to PHA, ConA, PWM) and modest changes in total white blood cell and lymphocyte levels have been noted in populations exposed to DDT/other OCP (McConnachie and Zahalsky, 1992;Backer, 1995;Vine et al, 2001). Our study also showed that PHA-M stimulation caused a significant increase in CD45RA + CD4 + lymphocyte levels among the PBMC from both SLE patients and healthy controls.…”
Section: Discussionsupporting
confidence: 66%
“…This might be a result of higher levels of p,p'-DDE and both α-and β-HCH in their blood. Sub-optimal lymphoproliferative activity (i.e., decreased responses to PHA, ConA, PWM) and modest changes in total white blood cell and lymphocyte levels have been noted in populations exposed to DDT/other OCP (McConnachie and Zahalsky, 1992;Backer, 1995;Vine et al, 2001). Our study also showed that PHA-M stimulation caused a significant increase in CD45RA + CD4 + lymphocyte levels among the PBMC from both SLE patients and healthy controls.…”
Section: Discussionsupporting
confidence: 66%
“…Companion animals, like cats and dogs, often share the immediate environment of people and have access to the same air, water, and food [6,26,27]. Livestock, including cattle, horses, and goats, on the other hand, can have increased exposure to certain environmental toxicants since they live in outdoor environments [22].…”
Section: Discussionmentioning
confidence: 99%
“…Dogs have been indicated as potential public health sentinels because of their close interaction with humans, particularly their owners, while presenting associations with common infectious agents and vectors (Backer et al, 2001;Schmidt, 2009;Schurer et al, 2012). Whereas true sentinels should reveal diseases without harboring them, dogs may become reservoirs for certain diseases such as visceral leishmaniasis (DantasTorres, 2009).…”
Section: Introductionmentioning
confidence: 99%